2008
DOI: 10.1111/j.1533-2500.2007.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neurostimulation in Supraorbital Neuralgia Refractory to Conventional Therapy

Abstract: Supraorbital neuralgia has been identified as an infrequent cause of headache that may prove very difficult to control pharmacologically. Peripheral nerve stimulation using electrodes to stimulate the nerve segmentally responsible for the zone of pain may constitute a management alternative in such cases. We present the case of a patient with headache because of posttraumatic supraorbital neuralgia, refractory to medical treatment, with good analgesic control after peripheral nerve stimulation. Peripheral nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
0
26
0
1
Order By: Relevance
“…Therefore, radiofrequency thermocoagulation should not be used as the preferred interventional treatment technology in clinical practice but can be used when nondestructive PRF treatment is ineffective or the efficacy lasts for a short time. Peripheral nerve stimulator treatment requires long‐term implantation of stimulation electrodes and a pulse generator, which might cause corresponding surgical trauma and complications such as electrode displacement and infection . The performance of PRF treatment is simple and can be completed under local anesthesia; the treatment time is short, and hospitalization for treatment is not necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, radiofrequency thermocoagulation should not be used as the preferred interventional treatment technology in clinical practice but can be used when nondestructive PRF treatment is ineffective or the efficacy lasts for a short time. Peripheral nerve stimulator treatment requires long‐term implantation of stimulation electrodes and a pulse generator, which might cause corresponding surgical trauma and complications such as electrode displacement and infection . The performance of PRF treatment is simple and can be completed under local anesthesia; the treatment time is short, and hospitalization for treatment is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although resection of the supraorbital nerve through open surgery or destruction of this nerve through minimally invasive percutaneous interventional therapy can relieve the pain, it inevitably causes numbness in the innervated region that severely affects the postoperative quality of life of patients. Some small case studies have reported that advanced peripheral nerve stimulation produces satisfactory efficacy in the treatment of supraorbital neuralgia; however, the long‐term efficacy and outcome have not been reported. The efficacy of decompressive neurosurgery of the supraorbital nerve is described in only a few case reports …”
Section: Introductionmentioning
confidence: 99%
“…There are single case reports of prolonged, severe headache after trauma which required treatment with local anaesthetic nerve blockade, as described in idiopathic cases 3. In both cases this provided relief; however, the pain recurred in one patient who required a peripheral nerve stimulator 1 7. In both these patients the initial trauma was relatively severe—being struck by a metal hook and losing consciousness in one case, and a 9 m fall causing facial fractures in the other.…”
Section: Discussionmentioning
confidence: 99%
“…Three subjects required lead revisions, two of whom had superficial infections responsive to oral medications. Single case reports of supraorbital nerve stimulation for supraorbital neuralgia and for the treatment of cluster headache have been published [25,26]. Slavin et al [27] reported on five patients undergoing supraorbital nerve stimulation for craniofacial pain.…”
Section: Peripheral Nerve Stimulationmentioning
confidence: 99%